Pemanfaatan Eco-Enzyme sebagai Pestisida Alami dan Solusi Pengelolaan Limbah di Sulobaja, Mamuju Tengah: Utilization of Eco-Enzyme as a Natural Pesticide and a Solution for Waste Management in Sulobaja, Mamuju Tengah - Aristya, Ganies Riza; Safitri, Della Thasya Liona; Utami, Mia; Syafei, Dio Rachmaputra; Dewi, Umi Rosita; Abiyyi, Muhammad Hawi Qabus; Muhammada, Khusnus Syifa; Ulfa, Siti Zakia; Sofyantoro, Fajar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Sulobaja Village, located in Tobadak District, Mamuju Tengah Regency, faces significant challenges in managing household organic waste, which is often discarded indiscriminately or burned, leading to environmental pollution and reduced water quality. This community service program aimed to enhance public awareness and skills in organic waste management through the production of eco-enzyme, a liquid derived from fermenting organic waste that can be used as a natural cleaner, liquid fertilizer, and pesticide. The program included several stages: initial observation, socialization, hands-on practice, evaluation, and follow-up. Socialization was conducted through educational sessions at the Sulobaja Village Hall, followed by practical training on producing eco-enzyme using household organic waste, molasses, and water. After one month of fermentation, the resulting eco-enzyme exhibited a dark brown color and a distinct acidic aroma, indicating a successful fermentation process. Participants showed a high level of enthusiasm, with over 70% expressing their willingness to continue production independently. The program successfully reduced household organic waste, improved soil fertility, and decreased the use of chemical-based household products. Furthermore, it encouraged the establishment of small production groups to ensure program sustainability. The results demonstrate that eco-enzyme production can serve as a practical and sustainable solution for organic waste management while providing economic and environmental benefits to the community. This program is expected to be replicated in other villages as a model for environmentally friendly waste management.